The first data on the lichens of the Mongun-Taiga cluster of the Ubsunur Hollow Biosphere Reserve: epigeic macrolichens - Y. V. Storozhenko; E. A. Davydov; L. S. Yakovchenko (Проблемы ботаники Южной Сибири и Монголии, 2020)
34 species of soil macrolichensare reported for the first time for Ubsunur Hollow Biosphere Reserve.The species belong to 15 genera and 6 families. Most of them are representatives of Parmeliaceae and the lichen generaPeltigera, Cladonia, Stereocaulon, and Cetraria. All studied species inhabit soil; some species also mosses, or plantdebris in addition. The studied species are characterized by fruticose (19 species) and foliose (15) growth form. Themajority of the marcolichens have been found in mountain tundras, alpine meadows and sparse larch forests.